THE ROLE OF GENDER STUDIES CENTER AND CHILD (PSGA) IAIN SALATIGA IN PREVENTING SEXUAL VIOLENCE PERSPECTIVE OF MAQASID SYARIAH - Nastangin; Aji Saputro (JIL : Journal of Indonesian Law, 2024)
Sexual violence and harassment is a very inhumane act. This is a violation of both religious and state regulations. Nowadays, there are so many cases of sexual violence committed by perpetrators. Cases of sexual violence can take various forms of women, for example rape. In fact, this case does not only happen to adult women but also to children who are still underage. In essence, woman is a noble figure who must be protected. Therefore, the researcher has two questions related to this research, that : What steps does the PSGA take in preventing sexual violence and what is the role of PSGA in preventing sexual violence perspective of Maqasid Sharia. This research uses a type of qualitative research, namely research that aims to understand phenomena about what is experienced by research subjects, for example behavior, perceptions, motivations, actions, etc., holistically, and in a descriptive way in form of words and language, in a special natural context and by utilizing various natural methods. The results of this research are first steps of PSGA in preventing sexual violence, that: socialization, holding training, conducting counseling, having campus regulations, preparing guidelines related to sexual violence, making SOP (Standard operating procedure) and forming student agents. These are the steps that have been taken by PSGA to prevent sexual violence. Second, role of PSGA in preventing sexual violence has been carried out well through: As the leading sector (driving force) for violence prevention at IAIN Salatiga, as the person responsible for socializing prevention of sexual violence and drafting regulations of Chancellor regarding prevention and handling of sexual violence. These roles, when viewed from the perspective of Maqasid Sharia, basically have same goal as one of the goals of Maqasid Sharia that to protect the soul and descendant. Because if sexual violence does not occur, lives and descendant can be protected, which is what the PSGA actually hopes for.